(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
EmQuestão Vol. 20, n. 1 (2014) Link de acesso ao número http://www.seer.ufrgs.br/index.php/EmQuestao/issue/view/2353/showToc